Monitoring travellers from Ebola-affected countries in New South Wales, Australia: what is the impact on travellers?. (December 2017) - Chan, Jocelyn; Patel, Mahomed; Tobin, Sean; Sheppeard, Vicky
Abstract Background Amidst an Ebola virus disease (EVD) epidemic of unprecedented magnitude in west Africa, concerns about the risk of importing EVD led to the introduction of programs for the screening and monitoring of travellers in a number of countries, including Australia. Emerging reports indicate that these programs are feasible to implement, however rigorous evaluations are not yet available. We aimed to evaluate the program of screening and monitoring travellers in New South Wales. Methods We conducted a mixed methods study to evaluate the program of screening and monitoring travellers in New South Wales. We extracted quantitative data from the Notifiable Conditions Information Management System database and obtained qualitative data from two separate surveys of public health staff and arrivals, conducted by phone. Results Between 1 October 2014 and 13 April 2015, public health staff assessed a total of 122 out of 123 travellers. Six people (5%) developed symptoms compatible with EVD and required further assessment. None developed EVD. Aid workers required lower levels of support compared to other travellers. Many travellers experienced stigmatisation. Public health staff were successful in supporting travellers to recognise and manage symptoms. Conclusion We recommend that programs for monitoring travellers should be tailored to the needs of different populations and include specific strategies to remediate stigmatisation.